Laboratory determination of thiopurine levels in paediatric patients with inflammatory bowel disease - Rafael Martín-Masot; María Pilar Ortiz Pérez; Natalia Ramos Rueda; Juliana Serrano Nieto; Javier Blasco-Alonso; Víctor Manuel Navas-López (Elsevier, 2020)
Introduction and objectives: Thiopurines are drugs widely used in patients for the maintenance of remission in inflammatory bowel disease. The optimal plasma levels are known, but there is controversy about whether the need for other drugs is reduced or cost-effective. The aim of this study is to describe the use of the optimised treatment with thiopurines in paediatric patients with inflammatory bowel disease followed up in this Unit since the introduction of determining the drug levels. Material and methods: A descriptive retrospective study was conducted in which the plasma values of 6-thioguanine (6-TGN), 6-methyl-mercapto-purine (6-MMP), and their ratios were analysed using liquid chromatography. Other variables were collected, such as clinical status, analytical and demographic variables of patients with inflammatory bowel disease followed up in this Unit. Results: A total of 72 patients were included, and 140 determinations of metabolites were performed. The 6-TGN levels were found to below the therapeutic range in 61.5% of patients (in 7 cases due to lack of adherence to therapy), and 6-MMP was in the toxicity range in 7.4%. After the determination of 77 specimens, some action was taken, such as modifying the dose, change of formula, or withdrawing the drug. Only 9 patients were scaled to a biological drug (13.4% of the total on single therapy). No association was found between the activity of the disease and the thiopurine levels. Conclusions: In our experience, the monitoring of thiopurine levels helped to modify the drug dose that the patient received, adjusting their therapeutic levels, and potentially avoiding the addition of new drugs. Resumen: Introducción y objetivos: Las tiopurinas son fármacos muy empleados para el mantenimiento de la remisión en pacientes con enfermedad inflamatoria intestinal. Se conocen cuáles son los niveles plasmáticos óptimos, y existe controversia acerca de si reducen la necesidad de otros fármacos o son coste-efectivos. El objetivo de nuestro estudio fue describir el uso del tratamiento optimizado con tiopurínicos en pacientes pediátricos con enfermedad inflamatoria intestinal seguidos en nuestra unidad desde la implementación de la determinación de niveles de fármaco. Material y métodos: Estudio descriptivo retrospectivo en el que se analizaron valores en plasma mediante cromatografía líquida de 6-tioguanina (6-TGN), 6-metilmercaptopurina (6-MMP) y sus cocientes, así como estado clínico y variables analíticas y demográficas de pacientes con enfermedad inflamatoria intestinal en seguimiento en nuestra unidad. Resultados: Se incluyeron 72 pacientes y se realizaron 140 determinaciones de metabolitos. En el 61,5% de las determinaciones los niveles de 6-TGN se encontraban por debajo del rango terapéutico (en 7 casos debido a falta de adherencia terapéutica), y en el 7,4% de las de 6-MMP estaban en rango de toxicidad. Tras la determinación de 77 muestras se tomó alguna actitud derivada, procediéndose a la modificación de dosis, al cambio de formulación o a la suspensión del fármaco. Únicamente 9 pacientes escalaron a fármaco biológico (13,4% del total que estaban en monoterapia). No se encontró relación entre la actividad de la enfermedad y los niveles de tiopurínicos. Conclusiones: En nuestra experiencia la monitorización de niveles de tiopurinas ayudó a modificar la dosis de fármaco que recibía el paciente, adecuando sus niveles terapéuticos y evitando potencialmente la adición de nuevos fármacos.